THE PROBLEMATIC OF INTERPRETATION IN THE SEMANTICS OF THE LITERARY TEXT BY ABDELKADER FEDOUH - AN APPROACH FROM THE PERSPECTIVE OF CRITICISM OF CRITICISM - Nadjoua DJEDDI & Belal MAHIDDINE (Ziglôbitha)
Abstract: Interpretive semiotics, a key critical approach, has significantly shaped contemporary literary studies, particularly in analyzing poetic texts. This study investigates the integration of semiotics and hermeneutics in Abdelkader Fedouh's methodology, emphasizing the distinction between Saussure's and Peirce's concepts of the sign. It explores the interpretive aspects of Fedouh's analysis of Algerian poetry, focusing on the dramatic element and its role. The research identifies Fedouh's use of hermeneutic principles to reveal hidden poetic meanings and his framing of semiotics as a socially contextualized critical tool. Additionally, it highlights his focus on utopia in contemporary Algerian poetry and the role of signs in expanding our worldview, addressing the contradictions of the creative self through dualities like opposition and resemblance. Keywords: Hermeneutics, Texts, Reader, Semiotics, Criticism of Criticism.